Theoretical study : analysis of automated flow lines using discrete-event simulation - Ali, Nor Azizah (2003)
Discrete-Event Simulation (DES) has been used extensively by companies for modelling and analysis of manufacturing systems, especially in evaluating the performance of a proposed system and choosing an appropriate design before actually implementing the proposed solutions. To demonstrate the advantage of DES, it was used as methodology in this project to analyze the performance of an Automated Flow Line, which is one of the basic concepts in manufacturing systems. A relevant artificial case study has been selected as a data source and experimentation on the developed models has been carried out using simulation software package called ServiceModel (version 3.5). Moreover, the result obtained from simulation model was evaluated according to the general terminology for analysis of Automated Flow Lines. The key parameters chosen are cycle time (T,), frequency of line stop per cycle (F), actual production time (T,), average hourly production rate (R,), average blocked (B,,), total hours of downtime (D), and line efficiency (E). Consequently, this dissertation has demonstrated the DES is a good method to analyze the performance of Automated Flow Lines, as well as a decisionsupport tool for management.